Implementation Strategyeco Fishing Portat the Hamadi Fish Landing Base (PPI), Jayapura City, Papua Province - Manalu, Janviter; Siahainenia, Armand Ronald; Siallagan, Johnson (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
This research aims to analyze the public perception of the environmental management system that has been implemented in Hamadi's fish landing base (PPI) and to provide policy strategy recommendations to Local Government regarding the Eco Fishing Port (EFP) implementation at Hamadi PPI. There are 5 aspects that will be examined in the application of eco fishing port concept in a Hamadi PPI, such as; how the environmental management system and the status of its application; how the integrated waste management system; what is the condition of the components of public service facilities; what matters the attention of the management of the fishing port in environmental management; and how the sanitary and hygienic conditions of fish landing sites (TPI). This research used descriptive qualitative method through surveys and interviews. SWOT analysis method used to identify an internal and external factor that influenced the implementation of the Eco Fishing Port, and to find out the best strategy recommendation in order to increase the quality of environment management system at Hamadi PPI. The analysis result shown that the rating value of internal factors (strengths and weaknesses) is 2.510 and the rating value of external factors (opportunities and threats) is -0.175.